2022
DOI: 10.1088/1755-1315/1026/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Condition assessment and renovation of an aged precast reinforced concrete multi-storey building

Abstract: This paper assesses the condition of a 45 years old precast reinforced concrete multistorey building and proposes innovative repair techniques for extending its service life. The residential building investigated consists of six floors, and each floor consists of 4 apartments with a total floor area of 900 m2. Initially, visual inspection was conducted to identify the extent of deterioration in all parts of the building, followed by field non-destructive and destructive tests to determine the root causes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…In general, the numerical analysis revealed that the use of the high-strength concrete could lead to further enhancement in the behavior of RC-BCJ compared to normal concrete joints. This is consistent with the results available in the literature [45][46][47][48][49]. Moreover, it is observed that changing the reinforcement type from steel to SMA caused no change in the peak load of the BCJ.…”
Section: Load Capacity Of Beam-column Jointssupporting
confidence: 92%
“…In general, the numerical analysis revealed that the use of the high-strength concrete could lead to further enhancement in the behavior of RC-BCJ compared to normal concrete joints. This is consistent with the results available in the literature [45][46][47][48][49]. Moreover, it is observed that changing the reinforcement type from steel to SMA caused no change in the peak load of the BCJ.…”
Section: Load Capacity Of Beam-column Jointssupporting
confidence: 92%